Incidence of Various Factors Contributing To Dystocia And Outcome Of Pregnancies - Jabeen, Sadaqat; Majeed, Shamim (Journal of Postgraduate Medical Institute, 2011)
348 cases of obstructed labour were studied for the incidence and various contributing causes. On the maternal side, illiteracy, ignorance about antenatal care and misuse of Oxytocin by untrained persons; i-e traditional birth attendants, were the main contributing factors. The commonest cause in primigravidae was uterine dysfunction, while in multigravidae, it was malpresentation (transverse lie), followed by macrosomic babies resulting in cephalo-pelvic disproportion. 46 percent ended in Caesarean section and 25 percent in forceps delivery. Morbidity rate was high in these patients.